Performance of Vegetative and Reproductive Characteristics of Multiple Outcomes (F1) of Maize (Zea mays L.) on Peat Soil applied Sludge and Ash of Oil Palm - sulthan sulaiman siddik; khairunnisa lubis; hot setiado (Universitas Sumatera Utara, 2019)
Maize is one of the staple food crops in Indonesian that must be developed its genetic diversity. The objective of this study was to obtain the appearance of vegetative and reproductive character of some F1 maize populations on peat soil stress with pH criteria of 5.9 and peat soil with sludge and ash of oil palm. The research was conducted at Setiabudi field, Tanjung Rejo sub-district, Medan city from April to August 2017. This research used Randomized Block Design (RAK) with 2 treatment factors. The first factor is the population consisting of 5 levels:A (NEI9008 x CLA46), B: (NEI9008 x CLA106), C: (CLA106 x NEI9008),D: (CLA16 x CLA84), E: (CLA84 x NEI9008) and the second factor is planting medium consisting of 3 levels is M1 (peat soil), M2 (peat soil + ash of oil palm), M3 (peat soil + sludge). The results showed that the interaction of planting media with F1 population of maize plant had significant effect on plant height character. The best media is found in M3 (peat soil + sludge).